Language and gesture in Chinese conversation - Chui, Kawai (London ; New York : Routledge, 2022)
"Language and Gesture in Chinese Conversation is a study of quantitative-qualitative analysis of linguistic-gestural instances from conversations among adult native speakers of Taiwan Mandarin. As the linguistic and the gestural manifestations in natural discourse are examined together in the form of the simultaneous expression of meaning across modalities, more details about speech, gesture, cognition, and discourse can be revealed. The study will focus on representational gestures, spontaneous manual configurations depictions of semantic information associated with the linguistic meanings The intended audience of this book includes scholars in a broad range of studies, including linguistics, language and gesture, human communication, cognition, cognitive neuroscience, social psychology, sociology, linguistic anthropology, speech pathology, and speech therapy"--
Language and Gesture in Conversation -- Language, Gesture, and Semantic Relationship -- Metaphors in Language and Gesture -- Time in Language and Gesture -- Language, Gesture, and Temporal Relationship -- Perspectives on Production of Gestures in Speech Communication.
Keywords: Speech and gesture -- Taiwan; Conversation analysis -- Taiwan; Chinese language -- Discourse analysis; Chinese language -- Social aspects -- Taiwan; FOREIGN LANGUAGE STUDY / General